Effect of two fertilization medium on the in vitro development of Creole bovine embryosne embryos - Goicochea Vargas, José (2021)
The objective of this study was to evaluate the in vitro embryo production rate up to the blastocyst stage with two fertilization media: FERT-TALP and modified TCM-199, grown in BOEC medium, from oocytes collected by aspiration of follicular ovaries of creole cows obtained from the slaughterhouse. In total, 281 oocytes were collected, 179 for FERT-TALP medium and 144 for modified TCM-199. The oocytes were subjected to the process of maturation, fertilization and embryo culture in vitro. An oocyte cleavage rate of 25.8% was obtained in FERT-TALP and 2.4% in modified TCM-199 at 18 hours post-fertilization. Likewise, at 48h, 87.7% of total cleavage was obtained in FER-TALP and 40.5% in modified TCM-199, whose percentage of embryos with 4 to 8 cells was 64.5 and 26.2%, respectively. In the morula and blastocyst phase, a rate of 10.3 and 3.9% was achieved in FERT-TALP, respectively, while none wwere achieved with the modified TCM-199 medium.